The Digital Empire: Google. A study on Google’s User Satisfaction Level. - Rui Yin Lee (Advances in Global Economics and Business Journal, 2023)
This paper focuses on investigating the factors influencing Google user's satisfaction levels. The level of user satisfaction is crucial for Google as it represents its ability to dominate in this ever-changing technological world. We have identified the relationship between the independent variables (security and privacy, reachable and widespread customer service, expected performance, perceived ease of use, perceived usefulness, and personalisation) and the dependent variables (user satisfaction). A survey was conducted by distributing the google forms to 150 respondents. Respondents answer the questionnaire based on a 5-point Likert scale ranging from 1 (strongly disagree) to 5 (strongly agree). We adapted 19 items to investigate how the factors had influenced the user satisfaction level from the previous study. A sample item that has been asked in the questionnaire is "Google is constantly updated with the latest information". Next, the collected data are analysed using the IBM SPSS Statistics 26. The results show that security and privacy, expected performance and personalisation are positively affect the Google's user satisfaction level. The most influential factor influencing user satisfaction is expected performance followed by security, privacy, and personalisation.